PELANGGARAN PRINSIP KESANTUNAN BERBAHASA SISWA KELAS VII-B MTs MUHAMMADIYAH 3 YANGGONG DALAM BERKOMUNIKASI DENGAN GURU - Abdul Ghoni Mahmudi; Lulus Irawati; Dwi Rohman Soleh (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2020)
This research describes the breach of politeness in learning Indonesian in class VII-B MTs Muhammadiyah 3 Yanggong, Ponorogo Regency. In the Indonesian learning process, especially in the topic "Speaking Indonesian properly and correctly" students should use polite language whenever communicating to the teacher. However, there are still many students who break the principle of politeness. This research used descriptive qualitative method—data collection using the observation method with note-taking and recording techniques. The results of this study indicate that there is a violation of all politeness maxims in learning Indonesian. A form of violating the maxims of wisdom is that students do not respond to their teachers by answering unserious or joking. Flouting of generosity maxims is shown by how students convey their intentions or wishes emotionally. The students violate the maxims of approbation, in which students criticize directly or frankly. Violation of the maxims of modesty is delivered by underestimating the partner. Violation of the agreement's maxims is indicated by students' attitude who do not respect their teacher's orders by speaking in a rude Javanese speech style or ngoko. The students break the maxims of sympathy by boasting or praising themselves in front of their teachers and classmates.